Astaxanthin Alleviates Inflammatory Response in Neonatal Necrotizing Enterocolitis Rats by Regulating NOD2/TLR4 Pathway - Xuandong Zhang; Yujia Luo; Rui Gu; Zhou Jiang (Gastroenterology Research and Practice)
Background. Necrotizing enterocolitis (NEC) is often associated with exaggerated activation of inflammatory response. Astaxanthin has been shown in studies to have a positive and advantageous effect on anti-inflammatory response. Hence, it is of great significance to study the protective effect of astaxanthin in NEC disease and its molecular mechanism. Objective. The present study was to investigate whether astaxanthin attenuates NEC rats and to explore its potential mechanism. Material and Methods. Hematoxylin-eosin staining was used to observe the pathological change of the intestinal tissue in NEC rats. Subsequently, we determined the anti-oxidative stress, anti-apoptosis, and anti-inflammation in astaxanthin with enzyme-linked immunosorbent assay kits, TUNEL staining, western blot, and immunohistochemistry assay. Furthermore, we added nucleotide-binding oligomerization domain 2 (NOD2) inhibitor to certify the molecular pathway of the astaxanthin in NEC rats. Results. Astaxanthin improved the pathological changes of the intestinal tissues. It restrained inflammation, oxidative stress, and protected cells from apoptosis in the intestinal tissue and serum of the NEC rats. Moreover, astaxanthin enhanced NOD2, whereas it suppressed toll-like receptor 4 (TLR4), nuclear factor-κB (NF-κB) pathway-related proteins. Apart from that, the NOD2 inhibitor offset the protective effect of the astaxanthin towards the NEC rats. Conclusion. The present study indicated that astaxanthin alleviated oxidative stress, inflammatory response, and apoptosis in NEC rats by enhancing NOD2 and inhibiting TLR4 pathway.